Integrasi Perangkat Daerah dengan Dokumen Rencana Pembangunan Jangka Menengah Daerah (RPJMD) di Kabupaten Banyuwangi - Anggraeny Puspaningtyas (DIA: Jurnal Administrasi Publik, 2017)
Many problems related to the process of development planning in the region is the existence ofÂ  â€œego sectoralâ€ between the government apparatus in carrying out development. It can be seen that each agency tends to emphasize its duties and functions in development activities. Less optimal process of implementation of development process due to lack of synergy between sectors and target. Limitations of funds as a stimulant are also not matched by the active role of local governments to emerge regulations to encourage superior sectors. The purpose of this study is to analyze the preparation of economic development plans based on local economic potential in Banyuwangi by using interactive planning approach. In national development planning as well as in regional development planning, planning approach can be done in two ways: sectoral and regional (region) approach. Interactive planning method used in this research, to make planning in the future based on current problems faced then designing planning design to overcome those problems.